2014
DOI: 10.1039/c4cp00779d
|View full text |Cite
|
Sign up to set email alerts
|

Density of state determination of two types of intra-gap traps in dye-sensitized solar cells and its influence on device performance

Abstract: The density of state (DOS) of intra-gap traps and the dynamics of electron transport of a dye-sensitized TiO2 solar cell were investigated by means of time-resolved charge extraction (TRCE). The intrinsic chemical capacitance of the TiO2 layer was separated from the parasitic capacitance of the FTO electrode, and was found to be dependent biexponentially on the photovoltage. It was shown that the shallow traps (>700 meV) differ from the deep ones (<350 meV) by the respective characteristic energy of 48 meV and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
62
0

Year Published

2015
2015
2019
2019

Publication Types

Select...
6

Relationship

5
1

Authors

Journals

citations
Cited by 30 publications
(63 citation statements)
references
References 51 publications
(74 reference statements)
1
62
0
Order By: Relevance
“…[51] Briefly,the substrate was fabricated by doctor-blade method, and the paste was prepared by admixing P25 TiO 2 particles into diethylene glycol solution of hydroxypropyl cellulose (10 wt %). [51] Briefly,the substrate was fabricated by doctor-blade method, and the paste was prepared by admixing P25 TiO 2 particles into diethylene glycol solution of hydroxypropyl cellulose (10 wt %).…”
Section: Methodsmentioning
confidence: 99%
“…[51] Briefly,the substrate was fabricated by doctor-blade method, and the paste was prepared by admixing P25 TiO 2 particles into diethylene glycol solution of hydroxypropyl cellulose (10 wt %). [51] Briefly,the substrate was fabricated by doctor-blade method, and the paste was prepared by admixing P25 TiO 2 particles into diethylene glycol solution of hydroxypropyl cellulose (10 wt %).…”
Section: Methodsmentioning
confidence: 99%
“…Recently,w er eported as imilar Q-V ph dependence and verified ab iexponential distribution of two types of trap states with differente nergy characters. [40] In spite of the aforementioned efforts, the correlationo fe nergy (shallow or deep) with spatial location (bulk or surface) of the intragap traps tate remains obscure. Accordingly,t he density of states (DOS) of the intragap traps needs to be examined in more detail over ab road range of energies.…”
Section: Introductionmentioning
confidence: 99%
“…[54,55] In recent years, we have reported that time-resolved charge extraction (TRCE) could act as another effective candidate to study quantitatively the DOS distribution in dye-sensitized solar cells, quantum-dot-sensitized solar cells, and perovskite solar cells. [56][57][58][59][60] However,asignificant limitation of these methods is that the tested system should be connected to as hort or open circuit,s ot hey are unable to investigate the trap states in intrinsic perovskite films without selected electrodes. In contrast, transient infrareda bsorption spectroscopy can be used to measure the DOS distribution of thin films, but it is not easy to identify the characteristic optical signals and the requirement of instrumentsa nd technology is relatively high.…”
Section: Introductionmentioning
confidence: 99%